Brain Gray Matter Abnormalities in First-Episode, Treatment-Naive Children with Obsessive-Compulsive Disorder - Cheng, Bochao; Cai, Wu; Wang, Xiuli; Lei, Du; Guo, Yingkun; Yang, Xun; Wu, Qizhu; Gong, Jianping; Gong, Qiyong; Ning, Gang (Frontiers in Behavioral Neuroscience, 2016)
Although several magnetic resonance imaging (MRI) studies have been conducted in children with obsessive-compulsive disorder (OCD), the brain structural abnormalities in OCD, especially in children, are not yet well characterized. We aimed to identify gray matter (GM) abnormalities in the early stage of pediatric OCD and examine the relationship between these structural abnormalities with clinical characteristics. Examinations of 30 first-episode, treatment-naive pediatric OCD patients without any comorbidities and 30 matched healthy controls (HCs) were performed with 3.0 T MRI. Voxel-based morphometry (VBM) following Diffeomorphic Anatomical Registration using Exponentiated Lie algebra (DARTEL) was used to conduct voxel-wise tests for group differences in regional gray matter volume (GMV). Compared to HCs, the patient group exhibited more GMV in the bilateral putamen and left orbitofrontal cortex (OFC) and less GMV in the left inferior parietal cortex (IPL). The GMV alternation in the right putamen of OCD patients was positively correlated with HAM-A scores, while the GMV alternation in the left IPL exhibited a trend to negatively correlate with HAM-A scores. Our current results suggest that the gray matter abnormalities were defined in the early stage of pediatric OCD. Moreover, these findings provided further evidence of brain GM abnormalities that are not only present in the classical fronto-striatal-thalamic circuit but also in the default mode network, which may represent the interaction of abnormally functional organization of both network in pediatric OCD.